Українська хемічна термінологія на роздоріжжі - Попович, Орест (Видавництво Національного університету “Львівська політехніка”, 2002)
Українці в Америці здебільша вживають “харківський” правопис з 1929 р., який теж взяв за основу для своїх термінологічних праць Анатоль Вовк. У відродженні української хемічної термінології перед ведуть фахівці з “Львівської політехніки”. Процесові українізації хемічної термінології суперечить проект Держстандарту України з 2000 р. НТШ-А та Український Термінологічний Центр Америки опротестували цей проект деукраїнізації хемічної термінології і подали свої контрпропозиції.

Ukrainian in America mostly use the “Kharkiv orthography” of 1929, which was also adopted by Anatole Wowk in his terminological dictionaries. In the rebirth of Ukrainian chemical terminology the scientists of the Lviv Polytechnic Institute lead the way. However, the proposed standardization issued by the Bureau of Standards of Ukraine in 2000 effectively bans the use of the Ukrainian names for chemical elements. The Shevchenko Scientific Society and the Ukrainian Terminological Center in America have lodged a formal protest against the above proposal and have offered their counter-proposal.